Constrained Bithiazoles: Small Molecule Correctors of Defective ΔF508–CFTR Protein Trafficking - Coffman, Keith C. (American Chemical Society, 2014)
[Image: see text] Conformationally constrained bithiazoles were previously found to have improved efficacy over nonconstrained bithiazoles for correction of defective cellular processing of the ΔF508 mutant cystic fibrosis transmembrane conductance regulator (CFTR) protein. In this study, two sets of constrained bithiazoles were designed, synthesized, and tested in vitro using ΔF508–CFTR expressing epithelial cells. The SAR data demonstrated that modulating the constraining ring size between 7- versus 8-membered in these constrained bithiazole correctors did not significantly enhance their potency (IC(50)), but strongly affected maximum efficacy (V(max)), with constrained bithiazoles 9e and 10c increasing V(max) by 1.5-fold compared to benchmark bithiazole corr4a. The data suggest that the 7- and 8-membered constrained ring bithiazoles are similar in their ability to accommodate the requisite geometric constraints during protein binding.